OUTSTANDING SPORTSMEN - Teshaboyeva Nafisa Zubaydulla qizi; Abduvahobova Sevara Sobirjon qizi (Ta'lim innovatsiyasi va integratsiyasi, 2024)
Annotation: Outstanding Sportsmen Throughout history, there have been many outstanding sportsmen who have achieved great success in their respective fields. These athletes have inspired millions of people around the world with their dedication, determination, and skill. These are just a few examples of the many outstanding sportsmen who have graced the world of sports. These athletes have achieved great success through their hard work, dedication, and determination. They have inspired millions of people around the world to pursue their dreams and to never give up. Outstanding sportsmen are not only successful in their chosen sport, but they also serve as role models for others. They show us what is possible if we set our minds to something and work hard to achieve it. They inspire us to be better athletes, better people, and to make a positive difference in the world.